Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/00005176-200101000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Smectite in the Treatment of Acute Diarrhea: A Nationwide Randomized Controlled Study of the Italian Society of Pediatric Gastroenterology and Hepatology (SIGEP) in Collaboration With Primary Care Pediatricians

Abstract: Smectite reduces the duration of diarrhea and prevents a prolonged course. It may therefore consistently reduce the costs of gastroenteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 10 publications
0
48
0
3
Order By: Relevance
“…Moreover, montmorillonite can coat the gastrointestinal mucosa and consequently improve the defensive function against aggressive factors (Yen, 2006). Montmorillonite is recommended as an over-the-counter medicine for treating acute and chronic diarrhea and irritable bowel syndrome (IBS), owing to its strong adsorption (Guarino et al, 2001, Ducrotte et al, 2005). In our previous study, we demonstrated that montmorillonite adsorbs dietary triglycerides and cholesterol and increases fecal lipid excretion, thereby preventing obesity in an HFD-fed rat model (Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, montmorillonite can coat the gastrointestinal mucosa and consequently improve the defensive function against aggressive factors (Yen, 2006). Montmorillonite is recommended as an over-the-counter medicine for treating acute and chronic diarrhea and irritable bowel syndrome (IBS), owing to its strong adsorption (Guarino et al, 2001, Ducrotte et al, 2005). In our previous study, we demonstrated that montmorillonite adsorbs dietary triglycerides and cholesterol and increases fecal lipid excretion, thereby preventing obesity in an HFD-fed rat model (Xu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Aunque la mayoría de las investigaciones con estas arcillas se han centrado en sus efectos para prevenir la intoxicación por aflatoxinas 195,196 , estas arcillas han demostrado su utilidad en el tratamiento de signos clínicos GI. Por ejemplo, un estudio en Italia de más de 800 niños con diarrea aguda mostró que una arcilla de tipo esmectita redujo significativamente la duración de la diarrea 197 . Investigaciones más recientes han confirmado este efecto benéfico de arcillas esmectitas en controlar la diarrea en un gran número de pacientes pediátricos 198 .…”
Section: Arcillas Mineralesunclassified
“…pregnancy (Dong and Feng, 2005;Guarino et al, 2001). Hydrotalcite, an anionic nanoclay -from the family of layered double hydroxides (LDHs) -is a popular antacid and is used because magnesium and aluminum metal oxides slowly hydrolyze regulating the pH to an optimum value without provoking a rebound effect in the stomach (Linares and Brikgi, 2006).…”
Section: Introductionmentioning
confidence: 99%